The Roles of Physical Activity and Inflammation in Mortality, Cognition, and Depressive Symptoms Among Older Mexican Americans. Issue 11 (9th September 2019) - Shih, I-Fan; Haan, Mary N; Paul, Kimberly C; Yu, Yu; Sinsheimer, Janet S; Ritz, Beate
Abstract: A higher level of physical activity (PA) is associated with decreased risk of mortality, dementia, and depression, yet the mechanisms involved are not well understood, and little evidence exists for Mexican Americans. With data from the Sacramento Area Latino Study on Aging (1998–2007), we used Cox proportional hazards regression to separately evaluate associations of baseline PA level with mortality, dementia/cognitive impairment without dementia (CIND), and depressive symptoms, and we estimated the mediating effects of inflammatory markers in additive hazard models. A low level of PA (<35 metabolic equivalent of task–hours/week) was associated with increased mortality (hazard ratio (HR) = 1.50, 95% confidence interval (CI): 1.20, 1.88), dementia/CIND (HR = 1.37, 95% CI: 0.96, 1.96), and depressive symptoms (HR = 1.23, 95% CI: 1.00, 1.52). A low PA level added 512 (95% CI: −34, 1, 058) cases of dementia/CIND per 100, 000 person-years at risk (direct effect), while, through a mediating path, interleukin 6 (IL-6) added another 49 (95% CI: 5, 94) cases, or 9% of the total effect. For mortality, 8%–10% of the PA total effect was mediated through IL-6, tumor necrosis factor α (TNF-α), or TNF-α receptors. None of the inflammatory markers mediated the association between PA and depressive symptoms. Our results suggest that antiinflammation (especially as assessed by IL-6 and TNF-α levels) may partly explain how PA protects against dementia/CIND and mortality.